PENGARUH PENGGUNAAN LABU SIAM (Sechium edule) DENGAN KONSENTRASI YANG BERBEDA TERHADAP MUTU ORGANOLEPTIK DAN KADAR SERATKERUPUK IKAN - Sepni Asmira; Putri Aulia Arza (LPPM UNIVERSITAS PERINTIS INDONESIA, 2015)
One of the problems of adequate nutrition dominant place in Indonesian society is the problem of indigestion. Consumption of fibers in sufficient quantity is very good for constipation and safe for sensitive stomach or intestinal inflammation. Dietary fiber can reduce the risk of cancer due to incomplete digestion system (Soedarya, 2009). Chayote is one of the foods that are rich in fiber in addition to vitamins and minerals. West Sumatra province is one of the provinces chayoteproduction continues to increase from year to year, especially in the highlands. Use of squash in society merely boiled as a vegetable. Hence the need for the expansion of the potential of squash as a food product, one of them as an additional raw material in foods such as fish crackers so high nutritional value. This study aims to determine the best formulation of making fish crackers modified squash with different concentrations were viewed by the results of chemical tests and organoleptic test analyze changes in the levels of fiber crackers before and after added squash.The study was conducted in two phases, namely first esearch and advanced research. Preliminary research include making fish crackers, organoleptic test and analysis of fiber content. Manufacture of modified fish crackers with chayote conjoined and organoleptic test was conducted in the Laboratory of food, STIKES Perintis West Sumatra and fiber content analysis in the laboratory Kopertis Region X. The results of organoleptic test fish crackers were added chayote shows the average - average level of A panelist on crackers color is brownish , the average level of A panelist on crackers aroma is neutral, the average - average level of A panelist on crackers are crunchy texture, the average - average preference level panelists to taste crackers are like. So than - average levels of most favored A panelist is on treatment D (addition of 150 grams of chayote). For the highest fiber content in treatment D (addition of chayote 150 g). More additions of chayote on the fish crackers can increase the fiber content in fish crackers.